Analisis Pengaruh Tinggi Terbang Drone Terhadap Ketelitian Geometri Peta Foto - Rangga Wikandaru; Ketut Gunawan; Anton Sudiyanto; Edy Nursanto; Tedy Agung Cahyadi; Yudha Krisna Suhendra; Rizky Ikhsan Luthfian Noor (Retii, 2019)
The value of geometry accuracy of aerial photographs is one of the important things that must be designed when going to acquire a photo map, and one of the factors that greatly influences the value of geometry accuracy is the flying altitude of the drones when acquiring aerial photographs. This paper aims to compare the geometrical accuracy of aerial photographs with different variations in altitude and henceforth become a reference in conducting aerial photographic data acquisition. The data used in this study are aerial photographic data and premark coordinate data obtained when conducting research. From the research results obtained horizontal geometry accuracy value in aerial photographs decreases when the flight height increases and the value of vertical geometry accuracy gets better when the flight height increases. From these results, it is determined that the optimal flying height in conducting aerial photo data acquisition. Keywords: Geometry Accuracy, flying altitude variations, aerial photo.